1968
DOI: 10.1038/icb.1968.174
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Some Australian Fauna to Infection With Foot and Mouth Disease Virus

Abstract: Summary Several species of Australian fauna were tested for their susceptibility to infection with foot and mouth disease virus. The majority of the fauna tested would support the multiplication of virus after either intramuscular or intradermal inoculation, although clinical signs of foot and mouth disease were rarely seen. The preferred sites for virus multiplication appeared to be the soft palate and pharynx in the red kangaroos, and the salivary glands in the water rats. The serum neutralizing antibody tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Snowdon (33) reported that many species of Australian mammals are susceptible to FMDY. Viral multiplication took place and antibody was produced but lesions were seen only in the tree and red kangaroos (Macropus spp.…”
Section: Species Affectedmentioning
confidence: 99%
“…Snowdon (33) reported that many species of Australian mammals are susceptible to FMDY. Viral multiplication took place and antibody was produced but lesions were seen only in the tree and red kangaroos (Macropus spp.…”
Section: Species Affectedmentioning
confidence: 99%
“…Besides farm animals, FMD also affects more than 30 wild ruminant species [224]. In natural infections, the main route of virus entry is the respiratory tract, and as few as one to ten infective particles can produce the disease [84,220].…”
Section: The Virus and The Diseasementioning
confidence: 99%
“…Camels also have a wide distribution, but have a low density with little association with susceptible animals except in times of drought. The tree kangaroo (Dendrologus matschei) , which under laboratory conditions is susceptible to infection with FMD virus (Snowdon 1968), has a very restricted distribution, a low density and its arboreal habits would decrease its effectiveness as a vector of FMD .…”
Section: Distribution and Density Of Wild Animals And Their Associatimentioning
confidence: 99%
“…Although Snowdon (1968) showed that FMD virus would multiply in the water rat (Hydromys chrysogaster), the susceptibility of other native rodents to exotic diseases is not known. It is likely, however, that a large proportion would be susceptible to infection with Aujeszky's disease virus, and some could be involved in a sylvatic cycle of Venezuelan encephalomyelitis.…”
Section: Native Rodentsmentioning
confidence: 99%
See 1 more Smart Citation